Implementation and Effectiveness of a Veterans Affairs–Based Comprehensive Lung Cancer Survivorship Program. Issue 3 (24th November 2021) - Rabe, Brian J.; Stafford, Jordan W.; Hassinger, Alisa D.; Swartzwelder, Harry S.; Shofer, Scott L.
Abstract : We investigated the effect of a 12-wk multimodal survivorship program on lung cancer survivors. Program components included home-based pulmonary rehabilitation, depression and anxiety treatment, chronic obstructive pulmonary disease medication optimization, and smoking cessation. We observed improvements in the domains of functional status, quality of life, and mental health. Abstract : Purpose: Few programs exist to address persistent impairment in functional status, quality of life, and mental health in lung cancer survivors. We aimed to determine whether a 12-wk multimodal survivorship program imparts clinical benefit. Methods: Any patient at the Durham Veterans Affairs Medical Center with lung cancer and a Karnofsky score of ≥60 could participate. Chronic obstructive pulmonary disease medications were optimized at the enrollment visit. Participants with a Hospital Anxiety and Depression Scale (HADS) score of >8 were offered pharmacotherapy and mental health referral. Participants did home-based exercise with a goal of 1 hr/d, 5 d/wk. They were called weekly to assess exercise progress and review depression/anxiety symptoms. Participants were offered pharmacotherapy for smoking cessation. Results: Twenty-three (50%) of the first 46 enrollees completed the full 12-wk program. Paired changes from enrollment to completion (mean ± SD) were observed in 6-min walk test (73.6 ± 96.9 m, P = .002), BODE (Body mass index, airflow Obstruction, Dyspnea, and Exercise) index (−1.45 ± 1.64 points, P < .001), Duke Activity Status Index (3.84 ± 7.12 points, P = .02), Fried Frailty Index (−0.588 ± 0.939 points, P = .02), modified Medical Research Council dyspnea scale (−0.619 ± 1.284 points, P = .04), Functional Assessment of Cancer Therapy-Lung Emotional subscale score (1.52 ± 2.96 points, P = .03), HADS total score (−2.63 ± 4.34 points, P = .02), and HADS Anxiety subscale score (−1.47 ± 2.29 points, P = .01). Conclusions: A comprehensive Lung Cancer Survivorship Program provides clinically meaningful improvements in functional status, quality of life, and mental health.